Islamic Business Ethics in the Digital Marketing Strategy of Ledre Bojonegoro MSMEs: Mitigating Tadlis E-Commerce Practices - Ahmad Mustofa Lutfi (Managing: Jurnal Bisnis dan Manajemen, 2026)
This study examines the application of Islamic Business Ethics among Ledre Micro, Small, and Medium Enterprises (MSMEs) in Bojonegoro to mitigate manipulation practices (tadlis) on e-commerce platforms. The extreme physical fragility of Ledre products presents a high risk of damage during logistics expeditions, which inherently triggers potential information tadlis by sellers aiming for instant profit. This research employs a descriptive qualitative method with a case study approach to deeply explore business actors' behavior. Primary data were collected through participatory observation via digital ethnography on online stores and in-depth interviews with five key MSME owners. Data analysis was conducted using the Miles and Huberman interactive model—encompassing data condensation, data display, and conclusion drawing—validated through source triangulation. The findings reveal that MSMEs have internalized the values of siddiq (honesty) and amanah (responsibility) by explicitly including damage-risk disclaimers in product descriptions, displaying authentic photo documentation without excessive editing, and implementing extra-thick packaging standards. Consumer complaint handling adopts the khiyar principle through proportional compensation schemes. It is concluded that compliance with Islamic business ethics in the virtual space does not decrease sales volume; rather, it transforms into a brand reputation-strengthening strategy, minimizes return rates, and guarantees long-term business sustainability.